(untitled) (AYUSHDHARA, 2024)
Puyalasa is one of the Sandhigata Vyadhi described by Acharya Sushruta and Vagbhata. It is presented with symptoms of discharge of Puya (pus), Pakwa shopha (swelling), Vrana (wound), Vedana (pain) with Tridosha dushti. Puyaalasa can be co-related with chronic dacryocystitis. It is an infection of the lacrimal sac, secondary to obstruction of the nasolacrimal duct at the junction of lacrimal sac, followed by stasis in the lacrimal sac, causing pain, redness, and swelling over the inner aspect of the lower eyelid and epiphora. In this case study 62-year-old female complaining of pus discharge, watering of eyes associated with swelling over the lacrimal sac in left eye for 3 weeks was treated with application of Jaloukavacharana, along with internally Gandhaka rasayana, Nimbadi guggulu, for 45 days. The results proved to be significant, on the basis of clinical assessment that Ayurvedic management with Jaloukavacharana, and internal medication on the lacrimal sac area offers effective result in the treatment of chronic dacryocystitis.